2020
DOI: 10.2147/idr.s240013
|View full text |Cite
|
Sign up to set email alerts
|

<p>Detection of Chromosomal and Plasmid-Mediated Quinolone Resistance Among <em>Escherichia coli</em> Isolated from Urinary Tract Infection Cases; Zagazig University Hospitals, Egypt</p>

Abstract: Introduction: Resistance to fluoroquinolones (FQ) in uropathogenic Escherichia coli (UPEC) has emerged as a growing problem. Chromosomal mutations and plasmidmediated quinolone resistance (PMQR) determinants have been implicated. Data concerning the prevalence of these determinants in UPEC in our hospital are quite limited. Purpose: To investigate the occurrence and genetic determinants of FQ resistance in UPEC isolated from urinary tract infection (UTI) cases in Zagazig University Hospitals. Patients and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
(50 reference statements)
3
16
2
Order By: Relevance
“…Among the detected qnr genes, qnrS International Journal of Microbiology showed the highest prevalence, which agrees with previous studies [47][48][49]. Although detected in only 4.65% of our isolates, qnrB gene was reported as one of the most abundant genes in other studies [39,45,50]. qnrC gene was absent in all tested isolates, which agrees with other studies [45,51,52].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the detected qnr genes, qnrS International Journal of Microbiology showed the highest prevalence, which agrees with previous studies [47][48][49]. Although detected in only 4.65% of our isolates, qnrB gene was reported as one of the most abundant genes in other studies [39,45,50]. qnrC gene was absent in all tested isolates, which agrees with other studies [45,51,52].…”
Section: Discussionsupporting
confidence: 92%
“…PMQR was detected in 36/43 (83.72%) phenotypically fluoroquinolone-resistant isolates. Several studies showed similar results [ 39 , 40 ]. Other studies that investigated PMQR genes recorded variations in their prevalence rate even in the same country [ 41 44 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, the acquisition of plasmid-mediated quinolone resistance (PMQR) genes has been increasingly reported in Enterobacteriaceae species in most parts of the world [ 22 , 23 ]. The co-existence of mutations in QRDR and PMQR genes could occur, and the accumulation of these different mutations was associated with high level quinolone resistance [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. There were also several reports that Enterobacteriaceae isolates, which are susceptible to quinolone, also had carried mutations in QRDR or PMQR genes [ 14 , 22 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The co-existence of mutations in QRDR and PMQR genes could occur, and the accumulation of these different mutations was associated with high level quinolone resistance [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. There were also several reports that Enterobacteriaceae isolates, which are susceptible to quinolone, also had carried mutations in QRDR or PMQR genes [ 14 , 22 , 28 , 29 , 30 ]. There was a report that this led to them showing no clinical response when CIP resistance was acquired by the quinolone resistance gene, even when CIP MIC was about 0.25–0.5 μg/mL [ 30 ].…”
Section: Discussionmentioning
confidence: 99%